Preferensi Bersarang dan Morfometrik Lebah Tanpa Sengat di Kabupaten Luwu, Sulawesi Selatan, Indonesia: Nesting Preferences and Their Morphometric Stingless Bees in Luwu Regency, South Sulawesi, Indonesia - Prastiyo, Andi; Rajab, Marwan; Irfan, Muhammad; Rahman, Abd. (Forestry Faculty of Hasanuddin University, 2025)
Stingless bees (Apidae: Meliponini) are pollinators in tropical ecosystems that show morphological and ecological variations between species. This study aims to identify nesting preferences and their morphometric characters of stingless bees in Luwu Regency, South Sulawesi, Indonesia. Data collection was carried out through field surveys to access nesting preferences of stingless bees by locating their natural nests and documenting them in different habitats, after which bee samples were measured to obtain morphometric data. Data were then analyzed using one-way Analysis of Variance (ANOVA), Pearson correlation, and hierarchical clustering with SPSS 30.1.1.1.. Observations showed that stingless bees preferred Lansium domesticum trees as nest locations (42.5%), with variations in nest height, elevation, and entrance size that differed significantly between species (p < 0.05). The results showed that Tetragonula fuscobaltea had the smallest body size (2.99 ± 0.05), while T. biroi was larger (3.97 ± 0.10 mm) and formed a contiguous morphometric cluster, where there were two main groups, with T. fuscobaltea separated from the other three species. Strong positive correlations were found between body characters (r > 0.95), while environmental variables such as elevation and nest height did not show significant relationships to morphometry. The results of this study are expected to be the basis for the identification of stingless bee species morphometrically, as well as supporting the development of natural habitat-based conservation and the improvement of local bee cultivation in Luwu Regency and the South Sulawesi region in general.